Tutur Candra Bherawa Pakeliran Theater: A New Process of Creation For Traditional Theater - I Gusti Putu Sudarta; Dru Hendro (Institut Seni Indonesia Denpasar, 2023)
Tutur Candra Bherawa Pakeliran Theatre is a total theatre work that explores and uses the elements of the art in Balinese Traditional theatre. This work uses a song as a means for storytelling, becoming a theatrical music presentation. The melodies and vocals are not only based on Balinese and Javanese traditions but also adapt and transform the styles of qawwali music (Sufi songs) and other spiritual songs. It is presented in the Sangita song form, accompanied by instrumental music and dance. The concept of this work is ngarcana sarining lango, described as bukti-mukti-jiwan mukti. The method of creation utilizes the Gandha Sesa composition technique. Bhasma Sesa is the framework for the play, dramatic plot, play script, and form of presentation.